Métodos de incorporação de calcário em um latossolo vermelho sob plantio direto - Buzzatti, Alexandre Stella (2010)
Chemical limitations in soil, to the root growth in cultivated plants, is one of the main problems for yield and stability of agricultural production. No tillage system, is a conservative management for excellence, without soil revolving, liming materials are applied on the surface, causing chemical gradient in the soil profile and root growth limitations due to the presence of aluminum levels within the toxic range. This study aimed to evaluate the lime incorporation methods effect on the plants in a Oxissol. Treatments consisted of no tillage with or without liming on the surface ½ SMP, chiseling and plowing after lime application 1 SMP for pH 5.5 and half requirement of 1 SMP for pH 6.0 applied before and after plowing. Six months after implementation of experiment, soil samples were collected for the physic-chemical analisys. The effect of these soil managements on wheat, barley and black oat yield and the soybean in the summer were also evaluated. Wheat and barley leaves were collected for leaf-analysis. Grain yield and yield components were evaluated. Results indicated both plowing and chiseling were able to incorporate lime into the soil down to 15 cm, decreasing chemical gradient and eliminating presence of toxic elements, improving soil chemical quality in deeper layer. Although these improvements did not provide better development neither higher grain yield for the crops two months (oat, wheat and barley) and eight months (soybean) after implementation of the experiment. Management did not affect organic matter content in soil. It was concluded that chiseling could be recommended when chemical or physical limitations, because this management mobilize less the soil and even so it incorporated the lime